2013
DOI: 10.1021/jp311283a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of Short-Chain Phospholipids in the Adsorbed Film and Micelles: Study by Surface Tension and Dilational Viscoelasticity Measurements

Abstract: The aggregate formation and surface adsorption of aqueous binary mixture of short-chain phospholipids, dihexanoyl-phosphatidylcholine (DC6PC), and dioctanoyl-phosphatidylcholine (DC8PC), were examined by surface tension and dilational viscoelasticity measurements. The concentration versus composition diagram of aggregate formation was constructed by analyzing the surface tension data. The diagram demonstrated a synergetic effect that even when the mole fraction of DC8PC in the aqueous solution was 0.02, worm-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The steady decrease in the CMC with the increase in the amount of BSA in the mixture supports the formation of mixed aggregates between BSA and surfactant. The break point of the plot of surface tension vs. log [surfactant] provides the values of critical aggregation concentration (CAC) [32]. The CMC values of the surfactants alone are in good agreement with those reported in the literature [33].…”
Section: Surface Activitysupporting
confidence: 81%
“…The steady decrease in the CMC with the increase in the amount of BSA in the mixture supports the formation of mixed aggregates between BSA and surfactant. The break point of the plot of surface tension vs. log [surfactant] provides the values of critical aggregation concentration (CAC) [32]. The CMC values of the surfactants alone are in good agreement with those reported in the literature [33].…”
Section: Surface Activitysupporting
confidence: 81%
“…This contrasts with publications in which one may identify modulus synergism in binary surfactant systems. In those studies, dilatational moduli synergism could only be identified for either a fixed total concentration , or a fixed tension condition, but not both. Modulus synergism may be observed in either the storage modulus, the loss modulus, or perhaps both moduli.…”
Section: Resultsmentioning
confidence: 96%
“…The binary 2:1 SDS/DTAB mixture at the kerosene/water interface exhibits storage-dominant moduli and a concentration-dependent synergism in both storage and loss moduli. In addition, binary systems exhibiting modulus synergism without tension synergism can also be found, such as SDS with nonionic ethoxylated ether C n EO m surfactants , and some binary mixtures of water-soluble short-chain phospholipids …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations